Pharmacological suppression of Nedd4-2 rescues the reduction of Kv11.1 channels in pathological cardiac hypertrophy - Zhang, Hua; Fu, Tian; Sun, Jinglei; Zou, Sihao; Qiu, Suhua; Zhang, Jiali; Su, Shi; Shi, Chenxia; Li, De-Pei; Xu, Yanfang (Frontiers in Pharmacology, 2022)
The human ether-á-go-go-related gene (hERG) encodes the pore-forming subunit (Kv11.1), conducting a rapidly delayed rectifier K+ current (IKr). Reduction of IKr in pathological cardiac hypertrophy (pCH) contributes to increased susceptibility to arrhythmias. However, practical approaches to prevent IKr deficiency are lacking. Our study investigated the involvement of ubiquitin ligase Nedd4-2-dependent ubiquitination in IKr reduction and sought an intervening approach in pCH. Angiotensin II (Ang II) induced a pCH phenotype in guinea pig, characterized by increased incidences of sudden death and higher susceptibility to arrhythmias. Patch-clamp recordings revealed a significant IKr reduction in pCH cardiomyocytes. Kv11.1 protein expression was decreased whereas its mRNA level did not change. In addition, Nedd4-2 protein expression was increased in pCH, accompanied by an enhanced Nedd4-2 and Kv11.1 binding detected by immunoprecipitation analysis. Cardiac-specific overexpression of inactive form of Nedd4-2 shortened the prolonged QT interval, reversed IKr reduction, and decreased susceptibility to arrhythmias. A synthesized peptide containing the PY motif in Kv11.1 C-terminus binding to Nedd4-2 and a cell-penetrating sequence antagonized Nedd4-2-dependent degradation of the channel and increased the surface abundance and function of hERG channel in HEK cells. In addition, in vivo administration of the PY peptide shortened QT interval and action potential duration, and enhanced IKr in pCH. We conclude that Nedd4-2-dependent ubiquitination is critically involved in IKr deficiency in pCH. Pharmacological suppression of Nedd4-2 represents a novel approach for antiarrhythmic therapy in pCH.